2017
DOI: 10.1186/s12939-016-0511-9
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of family caregiving for elderly population in southern Ghana: the case of a peri-urban district

Abstract: BackgroundHealth systems in low and lower-middle income countries, particularly in sub-Sahara Africa, often lack the specialized personnel and infrastructure to provide comprehensive care for elderly/ageing populations. Close-to-client community-based approaches are a low-cost way of providing basic care and social support for elderly populations in such resource-constrained settings and family caregivers play a crucial role in that regard. However, family caregiving duties are often unremunerated and their ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 17 publications
4
66
2
1
Order By: Relevance
“…It is evident that the direct and indirect costs incurred by caregivers is substantial, given the economic context of the study area. For instance, Addo et al [ 12 ] report that about 71% of caregivers in Ghana reported monthly income of less than $223, consistent with recent estimate that about 94% of caregivers (of elderly persons) in Ghana reported monthly incomes of less than $224 [ 40 ]. Therefore, failure to identify, measure and quantify these costs leads to an underestimation of the economic burden experienced by informal caregivers of persons with severe mental illness.…”
Section: Discussionsupporting
confidence: 57%
“…It is evident that the direct and indirect costs incurred by caregivers is substantial, given the economic context of the study area. For instance, Addo et al [ 12 ] report that about 71% of caregivers in Ghana reported monthly income of less than $223, consistent with recent estimate that about 94% of caregivers (of elderly persons) in Ghana reported monthly incomes of less than $224 [ 40 ]. Therefore, failure to identify, measure and quantify these costs leads to an underestimation of the economic burden experienced by informal caregivers of persons with severe mental illness.…”
Section: Discussionsupporting
confidence: 57%
“…Similarly, Papastavrou et al [ 29 ] found that females were more burdened than males and experienced chronic stress because of caregiving responsibilities for schizophrenics in Cyprus. Sex differences in the burden of care have also been reported in studies examining elderly care [ 30 ]. Such findings reflect broader societal realities and require more in-depth investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In other contexts (e.g., Ghana, Russia), economic burden of caregiving and the benefits of home-based versus institutional care are emerging social policy issues. 6 Caregiving among migrant households in many countries is associated with a clash of cultures or values around balancing different caregiving beliefs. 7 In both high-income countries (HICs) and LMICs, data are showing that the informal caregiver workforce predominantly comprises of women.…”
Section: Introductionmentioning
confidence: 99%